Potential Benefits of Black Chokeberry (Aronia melanocarpa) Fruits and Their Constituents in Improving Human Health - Ren, Yulin; Frank, Tyler; Meyer, Gunnar; Lei, Jizhou; Grebenc, Jessica R.; Slaughter, Ryan; Gao, Yu G.; Kinghorn, A. Douglas (Molecules (Basel, Switzerland), 2022)
Aronia berry (black chokeberry) is a shrub native to North America, of which the fresh fruits are used in the food industry to produce different types of dietary products. The fruits of Aronia melanocarpa (Aronia berries) have been found to show multiple bioactivities potentially beneficial to human health, including antidiabetic, anti-infective, antineoplastic, antiobesity, and antioxidant activities, as well as heart-, liver-, and neuroprotective effects. Thus far, phenolic compounds, such as anthocyanins, cyanidins, phenolic acids, proanthocyanidins, triterpenoids, and their analogues have been identified as the major active components of Aronia berries. These natural products possess potent antioxidant activity, which contributes to the majority of the other bioactivities observed for Aronia berries. The chemical components and the potential pharmaceutical or health-promoting effects of Aronia berries have been summarized previously. The present review article focuses on the molecular targets of extracts of Aronia berries and the examples of promising lead compounds isolated from these berries, including cyanidin-3-O-galactoside, chlorogenic acid, quercetin, and ursolic acid. In addition, presented herein are clinical trial investigations for Aronia berries and their major components, including cancer clinical trials for chlorogenic acid and COVID-19 trial studies for quercetin. Additionally, the possible development of Aronia berries and their secondary metabolites as potential therapeutic agents is discussed. It is hoped that this contribution will help stimulate future investigations on Aronia berries for the continual improvement of human health.